MODEL KUMON UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI PECAHAN SISWA KELAS III DI SD NEGERI MAJALENGKA KULON VII - Yuyun Dwi Haryanti; Siti Nurjanah (Universitas Sarjanawiyata Tamansiswa, 2018)
This research is conducted due to by the ongoing occurrence of the students’ low conceptual understanding in the mathematical fraction. The students perceived that mathematical fraction is difficult to understand because the use of learning models is not appropriate in the learning process. This study aims to improve the conceptual understanding of class III students through the application of the Kumon model. The method used in this study is a Class Action Research method by adopting the Kemmis Mc Taggart Model. This research was carried out in three cycles including planning, implementation, observation, and reflection. The subjects of this study were 21 students in the third-grade consisting of 17 men and 4women. The researchers employed formative test in each cycle and conducted observation towards the teacher and the students as the data collection technique. The results of the average completeness of student learning through formative tests in cycle I was 69.62 (48%), cycle II was 77.71 (71%), and cycle III was 84.67 (100%). The results of the observation on teacher in each cycle were cycle I was 2.7 (enough), cycle II was 3.2 (good) and cycle III was 4.4 (very good). The results of the observation on students in each cycle were cycle I was 2.6 (enough), cycle II was 3.0 (good) and cycle III was 3.9 (very good). Based on the research results, it can be concluded that the Kumon model can improve the conceptual understanding of third-grade students of Majalengka Kulon VII Elementary School, academic year of 2016/2017, in Majalengka District, Majalengka Regency.